III–4 The Impact of Low-Intensity Pulsed Ultrasound (LIPUS) on Spinal Fusion After Posterior Lumbar Interbody Fusion (PLIF) Procedure. Issue 5 (May 2015) - Yukawa, Yasutsugu; Ito, Keigo; Machino, Masaaki; Inoh, Hidehumi; Yoshihara, Hisatake; Yoshida, Go; Tsushima, Mikito; Satake, Kotaro; Nakashima, Hiroaki; Kamiya, Mitsuhiro; Muramoto, Akio; Ouchida, Jun; et al.
Abstract : Purpose: The goal of spinal fusion in the reconstructive spinal surgery is to achieve solid bony fusion between vertebral segments. The purpose of this study was to investigate the efficacy of low-intensity pulsed ultrasound (LIPUS) in enhancing fusion rate and bone formation after one-level posterior lumbar interbody fusion (PLIF). Methods: One-level PLIF procedure was performed in the patients with degenerative lumbar spinal stenosis between L1/2 and L5/S. Total 210 subjects were enrolled in this study prospectively, and randomly divided into 2 groups with LIPUS treatment after surgery (L-group), and without LIPUS treatment (NL-group). The patients in L-group underwent LIPUS treatment over the fusion level every day until 6 months after surgery. At week 24 and 48, the images obtained by X-ray and Dynamic computer tomography (flexion-extension CT) were evaluated. The state of bone union was classified from grade 1 (fusion) to grade 4 (non-union) in both evaluations. Results: Finally 83 patients in L-group and 86 patients in NL-group were analyzed. According to X-ray images, 30 patients (39%) in L-group and 29 patients (37%) in NL-group were evaluated as grade 1 at 24 weeks after surgery, then 61 patients (74%) in L-group and 55 patients (66%) in NL-group at 48 weeks. While according to flexion-extension CT images, 33 patients (47%) in L-group and 36 patients (51%) in NL-group were evaluated as grade 1 at 24 weeks, then 51 patients (70%) in L-group and 42 patients (63%) in NL-group at 48 weeks. L-group showed higher fusion rate based on both radiographic and CT evaluation at 48 weeks, although the difference was not statistically significant. Conclusions: LIPUS therapy may promote successful fusion after spinal interbody fusion.